European dimension of education (EDE) - Berengueras Pont, Mercè; Vera Mur, José María (Avances en Supervisión Educativa, 2016)
The communication aims to analyze the European dimension of education, in its current context, taking into account genesis and evolution. Its conceptual and legal framework is analyzed and its historical development and its limitations, concluding with their projections and future challenges. Communication complements the legal and regulatory references European level, issued by the European Council and education ministers, exposed and mentioned along communication.
Keywords: european dimension; european education policy; Green Paper; White Book